1993
DOI: 10.1038/363728a0
|View full text |Cite
|
Sign up to set email alerts
|

HIV induces thymus depletion in vivo

Abstract: Human immunodeficiency virus (HIV) disease is typified by declining CD4+ T lymphocyte counts in the peripheral circulation, a loss which may be secondary to accelerated destruction, to suppressed differentiation, and/or to sequestration of circulating cells into tissue spaces. As it is hard to distinguish between these possibilities in human subjects, the pathogenic mechanisms associated with HIV infection are unclear. In particular, little is known about the events that occur within infected lymphoid organs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
223
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(237 citation statements)
references
References 27 publications
11
223
3
Order By: Relevance
“…Our results are supportive of the results found in the SCID-hu thy/liv model that suggested HIV also inhibited early stages of thymocyte maturation [30]. Thus, HIV disrupts thymopoiesis by both direct infection of thymocytes as well as thymic epithelial dysfunction and destruction either through direct infection or a bystander inflammatory process, resulting in depletion of thymocytes and decreased de novo mature T cell generation [19][20][21][22][23]. Ultimate proof of thymopoietic potential in HIV infection will come from examination of thymopoiesis of HIV-infected thymuses from patients with AIDS and in clinical trials.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results are supportive of the results found in the SCID-hu thy/liv model that suggested HIV also inhibited early stages of thymocyte maturation [30]. Thus, HIV disrupts thymopoiesis by both direct infection of thymocytes as well as thymic epithelial dysfunction and destruction either through direct infection or a bystander inflammatory process, resulting in depletion of thymocytes and decreased de novo mature T cell generation [19][20][21][22][23]. Ultimate proof of thymopoietic potential in HIV infection will come from examination of thymopoiesis of HIV-infected thymuses from patients with AIDS and in clinical trials.…”
Section: Discussionsupporting
confidence: 80%
“…In addition there were clusters of HIV-infected CD34 + stem cells identified in the subcortical regions of these thymuses. HIV also disrupts thymopoiesis by direct infection of thymocytes [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Utilizing the SCID-hu thy/liv model that was then challenged with HIV-1, investigators demonstrated that thymopoiesis was impaired by direct infection of thymocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, experimental infection of mice with a number of bacteria (Listeria monocytogenes [6], Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Streptococcus pneumoniae [7]), viruses (murine cytomegalovirus [8], murine leukemia virus [9], HIV [10], and mouse hepatitis virus [11]), and protozoa (Toxoplasma gondii [12], and Trypanosoma cruzi) induces a severe lymphocytopaenia and marked thymus atrophy and loss of cortical lymphocytes. In addition, certain bacterial products and toxins, such as lipopolysaccharide (LPS) [13], enterotoxigenic E. coli enterotoxin [14] and mycobacterial cord factor (trehalos 6,6′-dimycolate) [15], also cause severe thymus damage.…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection of the human thymus is associated with thymic destruction and accelerated disease progression (42)(43)(44)(45)(46). Given the profound effects of IL-7 on the survival of human thymocytes, it is possible that IL-7 might prevent or attenuate HIV-mediated destruction of the thymus.…”
Section: Effects Of Il-7 On Hiv-infected and Uninfected Thymus In Scimentioning
confidence: 99%